Management of noncardiovascular comorbidities in patients with heart failure with reduced ejection fraction. Issue 6 (29th April 2021) - Gale, Stormi E.; Mardis, Andrew; Plazak, Michael E.; Kukin, Alina; Reed, Brent N.
Abstract: Patients with heart failure with reduced ejection fraction often have one or more noncardiovascular comorbidities. The presence of concomitant disease states is associated with worse outcomes, including increased risk of mortality, decreased quality of life, and increased healthcare resource utilization. Additionally, the presence of heart failure with reduced ejection fraction complicates the management of these comorbidities, including varying safety and efficacy of therapies compared to those without heart failure. This article will review the literature on the pharmacologic management of common noncardiovascular comorbidities—including chronic obstructive pulmonary disease, depression, diabetes mellitus, gout, chronic kidney disease, and iron deficiency—in patients with heart failure with reduced ejection fraction, as well as provide recommendations for appropriate treatment selection in this population.